Opportunistic Autoimmune Disorders Potentiated by Immune-Checkpoint Inhibitors Anti-CTLA-4 and Anti-PD-1 - Kong, Yi-chi M.; Flynn, Jeffrey C. (Frontiers in Immunology, 2014)
To improve the efficacy of immunotherapy for cancer and autoimmune diseases, recent ongoing and completed clinical trials have focused on specific targets to redirect the immune network toward eradicating a variety of tumors and ameliorating the self-destructive process. In a previous review (Kong et al., Ann. N.Y. Acad. Sci. 1183:222-236, 2010), both systemic immunomodulators and monoclonal antibodies, anti-CTLA-4 and anti-CD52, were discussed regarding therapeutics and autoimmune sequelae, as well as predisposing factors known to exacerbate immune-related adverse events. This review will focus on immune-checkpoint inhibitors, and the data from most clinical trials involve blockade with anti-CTLA-4 such as ipilimumab. However, despite the mild to severe immune-related adverse events observed with ipilimumab in ~60% of patients, overall survival averaged ~22-25% at 3-5 years. To boost overall survival, other monoclonal antibodies targeting programmed death-1 and its ligand are undergoing clinical trials as monotherapy or dual therapy with anti-CTLA-4. Therapeutic combinations may generate different spectrum of opportunistic autoimmune disorders. To simulate clinical scenarios, we have applied regulatory T cell perturbation to murine models combined to examine the balance between thyroid autoimmunity and tumor-specific immunity.